2020
DOI: 10.1590/1678-9865202033e200085
|View full text |Cite
|
Sign up to set email alerts
|

Government-subsidized restaurants in Brazil: an evaluation within the framework of food and nutrition security

Abstract: Objective The objective was to evaluate government-subsidized restaurants in southern Brazil according to current regulations and the National Food and Nutrition Security Policy. Methods An evaluation matrix was developed on the basis of a literature review, logic model, immersion in a government-subsidized restaurant, and workshops with experts in the field. The Government-Subsidized Restaurant Evaluation Matrix contemplates two dimensions: Political/Organizational, composed of the subdimensions Administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 20 publications
0
17
0
2
Order By: Relevance
“…However, the results of the research indicate that the capitals have not achieved satisfactory results regarding actions to provide access to food through structures capable of meeting the existing demands. Florianópolis stood out negatively regarding the Equipamentos Públicos de Segurança Alimentar e Nutricional (EPSAN, Public Infrastructure for Food and Nutrition Security), which are SISAN's operational structures aimed at the supply, distribution, and commercialization of meals or food [23]. Although Curitiba has a better evaluation than Florianópolis as to Equipamentos Públicos de Segurança Alimentar e Nutricional, a study carried out in the capital of Paraná identified an irregular distribution of these equipments, prioritizing regions where income is higher, which shows a territorial segregation in the FNS strategies of this municipality [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of the research indicate that the capitals have not achieved satisfactory results regarding actions to provide access to food through structures capable of meeting the existing demands. Florianópolis stood out negatively regarding the Equipamentos Públicos de Segurança Alimentar e Nutricional (EPSAN, Public Infrastructure for Food and Nutrition Security), which are SISAN's operational structures aimed at the supply, distribution, and commercialization of meals or food [23]. Although Curitiba has a better evaluation than Florianópolis as to Equipamentos Públicos de Segurança Alimentar e Nutricional, a study carried out in the capital of Paraná identified an irregular distribution of these equipments, prioritizing regions where income is higher, which shows a territorial segregation in the FNS strategies of this municipality [24].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 35 studies analyzed, four of them stand out for using as a premise the conception of PR as equipment for promoting HRAF [7,38,52,53], understood as a political, collective and accessible space for all [57].…”
Section: Popular Restaurants As Equipment For Promoting Human Right T...mentioning
confidence: 99%
“…The study by Oliveira et al [7] investigated PR in the south of Brazil using an evaluative matrix that bases its parameters and value judgment on the regulations governing PR, as well as those that include PR in the PNSAN as an EPSAN. The researchers found satisfactory results in the sub-dimensions related to the structure of the PR as a Unidade de Alimentação e Nutrição (Food and Nutrition Unity) mainly regarding the provision of adequate food and the administration of the equipment.…”
Section: Popular Restaurants As Equipment For Promoting Human Right T...mentioning
confidence: 99%
See 2 more Smart Citations